Genotype of Hepatitis B Virus Coinfection in Typhoid Patients - SUPIANA DIAN NURTJAHYANI; RETNO HANDAJANI (Indonesian Society for microbiology, 2015)
Typhoid fever can cause liver disorder and may result in complication. Studies revealed hepatic involvement in thypoid known as typhoid hepatitis. Our previous paper reported the existance of hepatitis B virus (HBV) coinfection in the serum of patients with typhoid using nested-polymerase chain reaction (PCR). Based on sequence divergence, HBV has been classified into 10 genotypes (A-J), which in prediction response and correlates with clinical outcome of chronic HBV infection. This study was conducted to determine the genotypes of HBV in typhoid patients coinfected with HBV in Tuban. Sera obtained from 5 typhoid patients positive HBV by nested PCR). Study was performed by direct sequencing BigDye V1.1 Terminator Cycle Sequencing kit and ABI Prism 310 Genetic Analyzer. Analys had been using the Genetix version 10 software to create the phylogenetic tree. Phylogenetic analysis showed 3 samples as genotype B and 2 two samples as genotype C.